2007
DOI: 10.1038/sj.eye.6702925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes, photopic contrast sensitivity, wavefront analysis, and patient satisfaction following cataract extraction and IOL implantation: aspheric vs spherical acrylic lenses

Abstract: Purpose To determine vision quality when testing two acrylic intraocular lenses (IOLs), AcrysofIQ and AcrysofSingle-Piece, after routine cataract extraction and IOL implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 14 publications
(13 reference statements)
2
38
1
3
Order By: Relevance
“…24 There is no standardized questionnaire or universally accepted grading system for dysphotopsia, and much depends on the phrasing of the questions and the patients' subjective responses. A paired-eye trial 11 found no difference in postoperative patient satisfaction between the aspheric Acrysof IQ IOL and the spherical Acrysof single-piece IOL, even though HOAs and spherical aberration were reduced with the aspheric IOL. The latter findings are similar to those in our study, in which there were no significant subjective differences in the questionnaire between the 2 IOLs no matter how the questions were grouped and analyzed; any small differences did not appear to be clinically significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…24 There is no standardized questionnaire or universally accepted grading system for dysphotopsia, and much depends on the phrasing of the questions and the patients' subjective responses. A paired-eye trial 11 found no difference in postoperative patient satisfaction between the aspheric Acrysof IQ IOL and the spherical Acrysof single-piece IOL, even though HOAs and spherical aberration were reduced with the aspheric IOL. The latter findings are similar to those in our study, in which there were no significant subjective differences in the questionnaire between the 2 IOLs no matter how the questions were grouped and analyzed; any small differences did not appear to be clinically significant.…”
Section: Discussionmentioning
confidence: 94%
“…9 Aspheric IOLs were designed to reduce the positive spherical aberration of the cornea, improving contrast sensitivity under nonphotopic conditions over that with standard spherical IOLs. [10][11][12][13][14][15] Some have even reported an improvement in distance visual acuity. 16 The Akreos Adapt AO (Bausch & Lomb) is an aspheric aberration-free IOL (data provided by the manufacturer).…”
mentioning
confidence: 95%
“…[2][3][4][5] Although various tests have been used to measure subjective visual function and health-related qualityof-life after aspherical IOL implantation, the degree of improvement remains unclear.…”
mentioning
confidence: 99%
“…23 Other studies have not found any difference in patient satisfaction comparing aspheric and spherical lenses. 24,25 Only one published study to date has compared different types of aspheric lenses. Johansson looked at the Tecnis Z9000 and Akreos AO lenses.…”
Section: Introductionmentioning
confidence: 99%